Fortification of curry powder with NaFe(111)EDTA in an iron-deficient population: report of a controlled iron-fortification trial - Ballot, D E; MacPhail, A P; Bothwell, T H; Gillooly, M; Mayet, F G (The American journal of clinical nutrition, 1989)
A targeted, double-blind controlled iron fortification trial using Fe(111)-EDTA in masala (curry powder) was directed towards an Fe-deficient Indian population for 2 y. The Fe status of the fortified group improved more than that of control subjects. Improvement reached significance over control subjects for females in hemoglobin (p = 0.0005), ferritin (p = 0.0002), and body Fe stores (p = 0.001) and for males in ferritin (p = 0.04). The prevalence of Fe-deficiency anemia (IDA) decreased from 22 to 5% in fortified females. Premenopausal women, multipara women, and women with prolonged menstruation or initial IDA benefitted most from fortification. The mean increase in body Fe stores in females with initial IDA was 9.0 +/- 1.3 mmol, representing an increased absorption of 12 mumol/d. Fortified subjects with normal Fe status did not accumulate excessive body Fe and there was no alteration in serum Zn concentrations. Targeted fortification is a safe and effective means of combatting Fe deficiency.